Penyusunan Laporan Keuangan Menggunakan MYOB Accounting Versi 18 Pada Toko Sepatu - Heri Ribut Yuliantoro (Politeknik Caltex Riau, 2015)
In daily activities shoe shop is still doing the recording manually and simply. Therefore, the writer did the research on the preparation of financial reports by using MYOB Accounting version 18. The goal of this research was to see the process of accounting and financial reports that would be generated after the computerized financial statement preparation is applied to shoe shop. The research was arranged based on the beginning balance and transactions that happened for 6 months in July, August, September, October, November, and December 2014 in shoe shop. This research would help shoe shop in presenting the financial statements including balance sheet, income statements, and cash flow statement for the year of 2014. shoe shop can save their time and become precise in recording their operational activities. This research can help other people that have the same case as shoe shop to apply the system in their business. The results of this research are the 6 month financial reports in 2014 of shoe shop. Key words: accounting process, financial report, and MYOB Accounting ver 18